INTEGRASI MANAJEMEN KELAS DAN KONTROL KEDISIPLINAN UNTUK MENGUBAH PERILAKU SISWA YANG TIDAK PRODUKTIF - Nugroho, Isfauzi Hadi (Jurnal al Hikmah, 2018)
Some administrators consider class management and discipline to be two things in common. explain class management is the behavior associated with managing the behavior of student tasks and reducing (reducing) behavior not doing tasks or destructive behavior. This view emphasizes effective class management as a process of controlling student behavior. The student-centered approach views classroom management as a way to prepare students' lives. This view emphasizes not on controlling student behavior at present but preparing students for students' lives for their future. Teachers and administrative staff who interpret this to mean effective class management is a process of creating a positive social and emotional climate in the classroom. This article will elaborate on how teachers and administrative staff are managing class management and the factors that determine their views.